Ageing effects after ozone and water immersion on tensile strength at room and high temperatures of carbon/epoxy F8552 laminates. (January 2021) - Cunha, JAP; Silva, TC; Costa, ML; Rezende, MC
Tensile tests were assessed to evaluate the ageing effects on carbon fiber/epoxy resin laminates exposed to ozone and water immersion. Laminates with distinct fiber arrangements (unidirectional - UD and plain weave - PW) were tested under transversal and longitudinal tensile strength at room (22°C) and high (88°C) temperatures after conditioning. The transversal tensile strength tests of UD laminates performed at room temperature show that the water immersion decreased this property in 28% when compared to non-conditioned samples. Ozone atmosphere also deteriorates the tensile strength considerably, drop of 27%. It was expected a higher drop in water immersion conditioning than in ozone atmosphere due to this conditioning attacks preferentially the external surface of specimen contrariwise the water immersion has diffusion inside the epoxy matrix. Tensile strength at high temperature shows more accentuated degradation for UD specimens exposed to water immersion (50% drop) than ozone (25%). Higher temperatures favor the degradation of the polymeric matrix and fibers/matrix interface. Tensile strength of PW laminates non-conditioned and conditioned with ozone, tested at room temperature, presented tensile strength results slightly different, 17% lower. When submitted to water immersion the results have dropped 26%, which are similar to unidirectional composite. At high temperature, PW laminate attacked with ozone had tensile strength reduced in 7%, while after water immersion the drop achieved 18%. These results show that water immersion affected the composite much more than ozone. Fractographic analyses confirmed that the combination between high temperature and conditioning promoted the degradation of matrix and fiber/matrix interface.